Evaluasi Kebijakan Dana Kampung dan Alokasi Dana Kampung Menggunakan Logic Model - Adrianus Adrianus; Muhammad Jamal Amin; Rulinawaty Rulinawaty (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
The aim of this research is to evaluate village fund management policies and village fund allocation in Muara Asa Village, Barong Tongkok District, West Kutai Regency using a logic model. This type of research is qualitative with a case study approach. The results of the research show that village funds in Muara Asa Village are used to build infrastructure such as building village roads every year, building village bridges, building physical facilities and infrastructure for village government offices, building health facilities and infrastructure, building and rehabilitating clean water sources, maintaining farming roads. , construction of road infrastructure such as sewers, and construction of public latrines (MCK). Village Fund allocations are used to improve Village Government services by building office infrastructure, financing operational costs and salaries for Village Officials, and holding training for Village Officials. Conclusion, the process of implementing Village Funds and Village Fund Allocation in Muara Asa Village is going well and in accordance with community needs. Keywords: Fund Allocation, Logic Model, Policy, Village Funds